2020
DOI: 10.1080/01490400.2020.1712282
|View full text |Cite
|
Sign up to set email alerts
|

Connecting to the trail: Natural spaces as places of healing

Abstract: The concept of "place" has been explored for decades, examining how specific geographic locales impact social meanings and interactions, sentimentality associated with a specific environment, and the construction of identity through prolonged place interaction. While meanings often differ based on individual history and interactions, physical environments are often symbolic; they may come to embody elements of potential, catharsis, restoration, or opportunity. In the context of nature, the diversity of meaning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 64 publications
(106 reference statements)
0
2
0
Order By: Relevance
“…The preservation and protection of natural sites has always been a topic much investigated by both the scientific community and land management entities (Evans 1975;Harmon and Kyle 2022). The objective is twofold, on the one hand to safeguard what can be defined as geosites (Calcaterra et al 2014), in terms of biodiversity and geological peculiarities, and on the other hand to improve the use by hikers and increase naturalistic awareness.…”
Section: Discussionmentioning
confidence: 99%
“…The preservation and protection of natural sites has always been a topic much investigated by both the scientific community and land management entities (Evans 1975;Harmon and Kyle 2022). The objective is twofold, on the one hand to safeguard what can be defined as geosites (Calcaterra et al 2014), in terms of biodiversity and geological peculiarities, and on the other hand to improve the use by hikers and increase naturalistic awareness.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, child and youth care practices have included therapeutic camps, sports, and recreational activities. Research in related fields such as human health protection and promotion has shown that contact with nature and recreational activities have a positive effect on addressing many psychological problems such as depression, anxiety, and behavioral disorders (Harmon & Kyle, 2022;Harper, 2017;Hutchinson et al, 2008;Mitchell & Popham, 2008;Frances, 2006;Huff et al, 2003). The benefits of the natural environment include reducing psychophysiological stress levels, increasing reflective capacities, and mental and physical recovery through access to and .Page 702 / 711.…”
Section: Introductionmentioning
confidence: 99%